Cascaded Integration of Optical Waveguides With Third-Order Nonlinearity With Lithium Niobate Waveguides on Silicon Substrates - Amirmahdi Honardoost (IEEE, 2018)
The cascaded integration of optical waveguides with third-order optical nonlinearity ( $χ ^{(3)}$ susceptibilitiy) with lithium niobate (LiNbO $_{3}$ ) waveguides is demonstrated on the same chip. Thin-film (LiNbO $_{3}$ ) and chalcogenide (ChG) glass (Ge $_{23}$ Sb $_{7}$ S $_{70}$ ) waveguides are integrated on silicon (Si) substrates. An optical mode transition between the two waveguides is achieved through low-loss mode-converting tapers, with a measured loss of $\sim$ 1.5 dB for transverse-electric and $\sim$ 1.75 dB for transverse-magnetic input polarizations. For nonlinear characterization, wavelength conversion via four-wave mixing is demonstrated on the ChG-LN waveguides. This platform provides an efficient method for the utilization of second- and third-order optical nonlinearities on the same chip, rendering it ideal for nonlinear applications such as stabilized octave-spanning optical frequency comb generation.